Talent Management Strategy in Retaining The Millennial Generation - Vitaharsa, Leonardo Indra (Economics and Business Journal (ECBIS), 2024)
The millennial generation, with its distinct characteristics and preferences, presents both challenges and opportunities for organizations in talent management. This study examines effective strategies to retain millennials in the workplace. Key findings reveal that millennials highly value continuous career development, a balance between work and personal life, and a collaborative and inclusive work environment. The adoption of advanced technology and frequent, constructive feedback are also crucial in engaging and retaining millennial employees. Organizations that adapt their talent management strategies to meet these needs are more likely to retain millennial talent and enhance long-term organizational success.